Respuesta agronómica de tres variedades de arveja (Pisum sativum L.) a la fertilización química y orgánica en la localidad de Laguacoto III, cantón Guaranda, provincia Bolívar - Ukuncham Jintiach, Irar Miguel (2016)
Peas are a legume of great importance for our food; is consumed abundantly, especially in green and in smaller scale like dry grain. This research was carried out in the Laguacoto III farm, canton Guaranda. The soil presented a clay loam texture, with a pH of 7.10 with an organic matter content of 2.5%. The objectives were: i) To study the agronomic response of three varieties of pea; ii) To evaluate the effect of chemical and organic fertilization on pea yield and iii) To make the Partial Budget Economic Analysis (AEPP) and calculate the Marginal Rate of Return (TMR%). A complete block design was applied randomly in factorial arrangement: Three varieties of pea with five types of fertilizers with three replicates. We performed variance analysis, Tukey's test at 5% for factor A; B and interaction of factors A x B; Correlation analysis and linear regression and economic analysis of partial presup and calculation of Marginal Rate of Return (TRM%). The response of the pea varieties to most of the performance components was very different. The highest average yield for factor A: (Varieties) was recorded in A1: INIAP - 435 Blanquita with 774 kg / ha in green and dry at 530.2 kg / ha. For factor B (chemical and organic fertilization), the highest yield in green was in B5: chemical optimum with 788 kg / ha and dry was B2: Ecoabonaza with 370 kg / ha. For the interaction of factors the treatments with the highest average value of yield were recorded in T10: INIAP - 436 Liliana + optimum chemical with 1010 kg / ha in green and dry T2: INIAP - 435 Blanquita + Ecuabonaza with 692, 33 Kg / ha. Economically it is more profitable pea in green with the variety INIAP-436 without the application of fertilizers and in reduced tillage. Critical factors affecting performance were drought and strong